2015
DOI: 10.3389/fnhum.2015.00130
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the effect of cognitive training on BDNF serum levels in individuals with Parkinson’s disease

Abstract: Parkinson’s disease (PD) patients, besides motor dysfunctions, may also display mild cognitive deficits (MCI) which increase with disease progression. The neurotrophin brain-derived neurotrophic factor (BDNF) plays a role in the survival of dopaminergic neurons and in the regulation of synaptic connectivity. Moreover, the brain and peripheral level of this protein may be significantly reduced in PD patients. These data suggest that a cognitive rehabilitation protocol aimed at restoring cognitive deficits in PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 95 publications
2
43
1
1
Order By: Relevance
“…There are several possible explanations for this, including the short training period; in order for cognitive training to cause a measurable increase in serum BDNF, prolonged training, i.e., over weeks, might be required. Promising and partial support for this approach already exists from two recent studies that found prolonged cognitive training to increase levels of serum BDNF in patients with heart failure [69] schizophrenia [70], and with Parkinson’s disease [71]. Related to length of training as a possible explanation for the lack of a BDNF effect from cognitive training and mindfulness in our study, is the possibility of a difference in serum BDNF origin between the different exercises we compared.…”
Section: Discussionmentioning
confidence: 53%
“…There are several possible explanations for this, including the short training period; in order for cognitive training to cause a measurable increase in serum BDNF, prolonged training, i.e., over weeks, might be required. Promising and partial support for this approach already exists from two recent studies that found prolonged cognitive training to increase levels of serum BDNF in patients with heart failure [69] schizophrenia [70], and with Parkinson’s disease [71]. Related to length of training as a possible explanation for the lack of a BDNF effect from cognitive training and mindfulness in our study, is the possibility of a difference in serum BDNF origin between the different exercises we compared.…”
Section: Discussionmentioning
confidence: 53%
“…High IL-6 levels have been associated with a variety of inflammation-associated diseases including rheumatoid arthritis [13], asthma [23] and obesity [24]. In contrast, lower IL-6 levels are associated with higher scores in positive relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cognitive training has been shown to reduce stress-related symptoms and improve sleep onset latency and efficiency in individuals with stress-related exhaustion (162) and in older adults with insomnia (163), respectively. The regulation of stress symptoms and improved sleep efficiency could facilitate an increase in BDNF, which has been reported following cognitive training in individuals with PD (164).…”
Section: Effects Of Multidisciplinary Therapy On Brain Volume and Potmentioning
confidence: 98%